Film copyright in the European Union - Kamina, Pascal (Cambridge, UK ; New York : Cambridge University Press, 2002)
In the first book on this subject, Kamina analyses film protection in the fifteen member states of the EU, with emphasis on Britain and France. He addresses key aspects of film copyright, including the protection of film works within the EU in the context of European harmonization of copyright laws.
Cover; Half-title; Series-title; Title; Copyright; Contents; Foreword; Preface; Acknowledgments; Abbreviations; 1 Introduction; 2 The history of film protection in Europe; 3 Subsistence of copyright; 4 Authorship and initial ownership; 5 Copyright transfers and authorial rights; 6 Exclusive rights; 7 Exemptions and permitted acts; 8 Moral rights in films; 9 Performers' rights; 10 Protection of foreign film works; Appendix 1: A basic guide to the European Union; Appendix 2: Principal national copyright legislation; Appendix 3: EC copyright directives.
Includes bibliographical references and index.
Print version record.
English.
eBooks on EBSCOhost
Keywords: Copyright -- Motion pictures -- European Union countries; Copyright -- Motion pictures -- Great Britain; Copyright -- Motion pictures -- France; Droit d'auteur -- Cinéma -- Pays de l'Union européenne.; Droit d'auteur -- Cinéma -- Grande-Bretagne.; Droit d'auteur -- Cinéma -- France; LAW -- Administrative Law & Regulatory Practice; Copyright -- Motion pictures; European Union countries; France; Great Britain; Auteursrecht; Films; Europees recht; Electronic books; Electronic books